دور الحكومة الإلكترونية في تحسين جودة الخدمة دراسة ميدانية على عملاء فروع المصرف التجاري السوري في محافظة اللاذقية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدف البحث إلى التعرف على مدى تطبيق الحكومة الإلكترونية في المصارف الحكومية، من خلال التعرف على أثر تطبيقات الحكومة الإلكترونية السائدة حالياً في المصارف محل الدراسة على تحسين أبعاد جودة الخدمة المتعلقة بالاعتمادية والاستجابة والأمان والتعاطف والجوانب المادية. وقد أشارت نتائج البحث إلى وجود فروق جوهرية بين أبعاد جودة الخدمة المتوافرة حالياً في المصارف محل الدراسة وبين أبعاد جودة الخدمة الواجب توافرها وفقاً للحكومة الإلكترونية. كما أشارت نتائج البحث إلى انخفاض رضا العملاء عن خدمات الصراف الآلي، والخدمات المتاحة من خلال شبكة الإنترنت. وتمثلت أهم توصيات البحث بضرورة قيام المصارف بتقديم الخدمة بشكل صحيح من أول مرة وفي كل مرة وفي الوقت المناسب، وتبسيط إجراءات الحصول على الخدمة، والرد على استفسارات العملاء بشكل سريع، واحترام خصوصية المعلومات المتعلقة بالعملاء، وخاصة المتعلقة بالحسابات الشخصية، وتوجه العمليات المصرفية باحتياجات العملاء، وتوفير الحواسيب والأجهزة والبرامج المتطورة القادرة على التعامل مع تقنيات الحكومة الإلكترونية، وتوفير الأمن المعلوماتي المتعلقة بجميع عمليات المصرف، والعمل على التحول إلى مرحلة الموقع التبادلي للمصرف الإلكتروني. This research aims at identifying the extent of applying electronic government in government banks by identifying the impact of electronic government applications currently used in the banks under study to improve the dimensions of service quality  which are related to reliability, responsiveness and security, compassion, and some  physical aspects. The results of this research reveal the existence of significant differences between the dimensions of service quality currently available in the banks under study and between the dimensions of service quality that should be available according to the electronic government. The results have also referred to low levels of  customer satisfaction with ATM services, and services available on the Internet. The most important recommendations of the research are the need for banks to provide services correctly at the first time and at every time, and to simplify procedures of  obtaining services. It has also recommended responding  to customer inquiries quickly, respecting the privacy of customers' information, especially those related to personal accounts, and providing computers, hardware and advanced software capable of dealing with electronic Government technologies. In addition, the research also promotes providing information security for all bank operations, and working on the transition to interactive website of the electronic bank.